The profile of university professors in Social Studies courses at Costa Rican state universities (Innovaciones Educativas, 2023)
The article discusses the results of the first phase of a research in history didactics whose object of study is the social representations on history and its teaching in initial teacher training. The objective of the paper is to characterize the profile of teachers who teach history and pedagogy in undergraduate courses (high school and undergraduate) in the teaching of Social Studies and Civic Education in Costa Rican state universities. The research was developed from a qualitative and interpretative approach, with the support of quantitative data analysis techniques such as graphs to measure trends, two data collection techniques were used: the questionnaire and the interview, with the purpose of knowing who is in charge of training the trainers in the area of social sciences and how this explains the model of initial teacher training in the careers of Social Studies in Costa Rica. The analysis of the information was done through quantitative description of the data, thematic coding and triangulation. The results show that the profile of the university teacher is based on specialized knowledge of the historical discipline.
Keywords: specialized teacher; higher education; social studies; history teaching; teacher education